PENGARUH KOMPETENSI, KOMUNIKASI, DAN TEKANAN WAKTU TERHADAP KUALITAS HASIL PEMERIKSAAN PAJAK - Ahmad Syarif Kurniawan; Ayu Chairina Laksmi (Jurnal Ekonomi Dan Bisnis, 2021)
This study aims to examine the effect of tax auditor competence, communication skills, and time pressure on the quality of tax audit outcome. The research method used is quantitative by collecting data using a survey method by distributing questionnaires to 130 tax auditors at the Tax Service Office at the Regional Office of the Directorate General of Taxes, East Java I. The analytical tools used in this research is multiple linear regression and data analysis in this study uses the Statistical Package for the Social Sciences (SPSS) version 25th.The results showed that tax auditors' competence and communication skills partially had a positive effect on the quality of tax audit outcome, while time pressure had no effect on the quality of tax audit outcome. Simultaneously, the tax auditor's competence, communication skills, and time pressure have an effect on the quality of the tax auditor outcome.